Financial literacy and environmental sustainability: a cross-country test - Salahodjaev, Raufhon; Sadikov, Avazbek (Frontiers in Sustainability, 2025)
IntroductionAn increasing number of countries are facing environmental pressure due to factors such as industrialization, rapid economic growth, the overuse of natural resources, energy consumption, and financial crises. We analyzed data from a sample of 131 countries for the period 2000–2024, allowing for the consideration of key factors influencing environmental degradation and testing the hypothesis that nations with higher levels of financial literacy are better positioned to advance toward a sustainable future.MethodsThis study uses two variables as proxies for environmental sustainability. Our first dependent variable is the Environmental Performance Index (EPI) for the year 2024. Our second indicator is the ND GAIN Index presented by the Notre Dame Global Adaptation Initiative. The ND GAIN Country Index is composed of two key dimensions of adaptation: vulnerability and readiness. Considering that financial literacy data are only available at cross-sectional levels, we estimate the relationship between environmental sustainability and financial literacy using the ordinary least squares (OLS) estimator with heteroskedasticity-adjusted robust standard errors.ResultsThe bivariate association between financial literacy and EPI suggests that a one standard deviation increase in financial literacy is associated with more than a half standard deviation increase in EPI. The results show that GDP has a non-linear relationship between GDP per capita and environmental indicators, while globalization enhances environmental sustainability.ConclusionFrom the baseline results, we document that the financial literacy of a population is associated with improvements in environmental quality across countries, thus providing additional evidence that financial literacy not only improves financial wealth/capital preservation but also preserves environmental wealth/capital. We also document that financial literacy is an important determinant of environmental sustainability even after controlling for democracy and economic development. This implies that it is crucial to invest in financial literacy even in lower-income countries. The series of robustness tests offer clear evidence that financial literacy is an essential antecedent of environmental sustainability and should be taken into account in long-term policy planning.